Representations of Political Leadership Qualities in News Coverage of Australian and Canadian Government Leaders. Issue 3 (September 2022) - Wagner, Angelia; Trimble, Linda; Curtin, Jennifer; Auer, Meagan; Woodman, V. K. G.
ABSTRACT: How do the media depict the leadership abilities of government leaders, and in what ways are these depictions gendered? Does the focus of leadership evaluations change over time, reflecting the increased presence of women in top leadership roles? To answer these questions, we examined news coverage of 22 subnational government leaders in Australia and Canada, countries in which a significant number of women have achieved the premiership at the state or provincial level since 2007. Analysis demonstrates that newly elected women and men leaders receive approximately the same number of leadership evaluations. Women are assessed based on the same criteria as men. All subnational political leaders are expected to be competent, intelligent, and levelheaded. That journalists prioritize experience and strength while downplaying honesty and compassion indicates a continued emphasis on "masculine" leadership norms in politics. Yet evaluations of new premiers have emphasized the traditionally "feminine" trait of collaboration as key to effective leadership and, over time, have given more attention to likability and emotions when covering male premiers. As our analysis reveals, media conceptualizations of political leadership competencies are slowly expanding in ways that make it easier for women to be seen as effective political leaders.